1989
DOI: 10.1111/j.1540-6288.1989.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Day‐of‐the‐Week Effects in Four Emerging Stock Markets

Abstract: The “January effect” and the “weekend effect” have proven to be persistent anomalies in U.S. equity markets. The objective of this paper is to examine seasonal and daily patterns in equity returns of four emerging markets: Hong Kong, Singapore, Malaysia, and the Philippines. These markets are gaining importance with the globalization of business; therefore, it is necessary to examine the efficiency and functioning of these capital markets. Our analysis uses daily data for the 12 years from September 1, 1976, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(80 citation statements)
references
References 22 publications
7
68
2
3
Order By: Relevance
“…The implication of ADF test result for investors is that the better forecast the stock return by analyzing past trend of securities in KSE. The result match with those studies done in emerging economy like Poshakwale, Mehdian and Perry, Aggarwal and Rivoli, Aly et al and Guidi et al [8][9][10][11][12].…”
Section: Augmented Dickey-fuller Testsupporting
confidence: 81%
See 1 more Smart Citation
“…The implication of ADF test result for investors is that the better forecast the stock return by analyzing past trend of securities in KSE. The result match with those studies done in emerging economy like Poshakwale, Mehdian and Perry, Aggarwal and Rivoli, Aly et al and Guidi et al [8][9][10][11][12].…”
Section: Augmented Dickey-fuller Testsupporting
confidence: 81%
“…This weekend effect is tested all over the world and reported for policy implication and restoring investors' confidence. Monday have significant effect in stock exchange and day of week effect exists in major stock exchange of world as reported [8][9][10][11]. Theories of finance give possible explanation of this weekend anomaly, but researchers thrust is still unfulfilled about it.…”
Section: Literature On Monday Effectmentioning
confidence: 99%
“…The day of the week patterns have been investigated extensively in different markets. Studies (Cross 1973;French 1980;Keim and Stambaugh 1984;Rogalski 1984;Aggarwal and Rivoli 1989) document that the distribution of stock returns varies according to the day of the week. The average return on Monday is significantly less than the average return over the other days of the week.…”
Section: Introductionmentioning
confidence: 99%
“…The liquidity of investors is higher in the month of January which increases the trading volume and increases the stock prices in the month of January (Ligon, 1997). Aggarwal and Rivoli (1989) examined calendar anomalies for the Hong Kong, Singapore, Philippines and Malaysia stock markets. They found that Philippines market is eficient and no one can gain the abnormal return in January since the January anomaly does not persist in Philippines stock market whereas in case of Hong Kong, Singapore, and Malaysia there is reverse state of affairs.…”
Section: January Effectmentioning
confidence: 99%